The Roles of Brackish Water Aquaculture in Fish Supply and Food Security in Some Coastal Communities of Rivers State, Nigeria - Ojo Andrew Akinrotimi; Olajunmoke Modupe Edun; Evans Williams Ibama (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2015)
Background and Aim: Fish plays a crucial role in human nutrition and food supply across the globe, particularly among the poor segment of the society. Food fish currently represents the major source of animal protein needed for growth and development, especially among the children and women who are more vulnerable to malnutrition in developing countries. The importance of food to an individual and society cannot be over emphasized, as food is a basic necessity of life and sufficient intake of quality food is imperative for people to live a strong, vibrant and productive life. Considering the importance of fish food, this study therefore assessed the contribution of brackish water fish farming to stable fish supply and food security in coastal communities of Rivers State. Methods: The roles of brackish water aquaculture in fish supply and food security in 10 coastal communities of Rivers State were investigated using structured questionnaires. The results obtained revealed that majority (56.5%) of the respondents were males, within the age bracket of 36 -50 (36.0%), with house hold size of 6-10 (48.5%). Also, most of the respondents (55.0%) had secondary education. The prominent (20.0%) primary occupations of the respondents include: schooling, fishing aquaculture and fish processing. Results: The result further revealed that Tilapia species is the most consumed fish (26.0%). In analysis of the sources of fish consumed by the respondents, most of the fish comes from fishing (45.0%), 37.0% from aquaculture and 18.0 %, from imported frozen fish. Assessing the role of aquaculture as a source of fish food, the respondents believed that aquaculture ensures regular supply (27. 5%), accessibility (25.0 %), low price (20.0%), big size (12.5%) clean (7.5%), good packaging (5. 0 %) and value addition (2.5%) of fish. Conclusion: It is of note that aquaculture plays a crucial role in regular supply andaccessibility of fish,  which will enhance food security in these coastal areas.